ATP-Dependent Transport of Leukotrienes B4 and C4 by the Multidrug Resistance Protein ABCC4 (MRP4) - Rius, Maria; Hummel-Eisenbeiss, Johanna; Keppler, Dietrich (The Journal of pharmacology and experimental therapeutics, 2008)
The proinflammatory mediators leukotriene (LT) B4 and LTC4 must be transported out of cells before they can interact with LT receptors. Previously, we identified the multidrug resistance protein ABCC1 (MRP1) as an efflux pump for LTC4. However, the molecular basis for the efflux of LTB4 was unknown. Here, we demonstrate that human ABCC4 mediates the ATP-dependent efflux of LTB4 in the presence of reduced glutathione (GSH), whereby the latter can be replaced by S-methyl GSH. Transport studies were performed with inside-out membrane vesicles from V79 fibroblasts and Sf9 insect cells that contained recombinant ABCC4, with vesicles from human platelets and myelomonocytic U937 cells, which were rich in endogenous ABCC4, but ABCC1 was below detectability. Moreover, human polymorphonuclear leukocytes contained ABCC4. Km values for LTB4 were 5.2 μM with vesicles from fibroblasts and 5.6 μM with vesicles from platelets. ABCC4, with its broad substrate specificity, also functioned as an ATP-dependent efflux pump for LTC4 with a Km of 0.13 μM in vesicles from fibroblasts and 0.32 μM in vesicles from platelets. However, GSH was not required for the transport of this glutathionylated leukotriene. The transport of LTC4 by ABCC4 explains its release from platelets during transcellular synthesis. ATP-dependent transport of LTB4 and LTC4 by ABCC4 was inhibited by several organic anions, including S-decyl GSH, sulindac sulfide, and by the LTD4 receptor antagonists montelukast and 3-(((3-(2-(7-chloro-2-quinolinyl)ethenyl)phenyl)-((3-dimethyl-amino-3-oxopropyl)-thio)-methyl)thio)propanoic acid (MK571). Thus, as an efflux pump for the proinflammatory mediators LTB4 and LTC4, ABCC4 may represent a novel target for anti-inflammatory therapies.